Inuit Women Working in the Nunavik Justice System: A Relational Perspective on Justice - Hervé, Caroline; Laneuville, Pascale (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2022)
The literature on how Inuit women relate to justice has thus far portrayed them largely as victims of various types of violence and in need of assistance. However, justice does not concern them only as victims, offenders, or affected family members, as many of them work in this field as crucial actors for their communities, providing people in difficulty with support and helping them navigate a complex structure. This article emphasizes the important role of Nunavik Inuit women today in maintaining community harmony. We also explore their views on the justice system and outline what an Inuit system of justice could look like today. Our research project used a participatory methodology, an ontological approach, and both qualitative and quantitative methods. Our results suggest that Nunavik justice is not simply a legal institution and should therefore be defined much more broadly and incorporate the moral principles of social responsibility and interdependence.